South Carolina scalawags - Rubin, Hyman, 1971- (University of South Carolina Press, 2006)
"South Carolina Scalawags tells the familiar story of Reconstruction from a mostly unfamiliar vantage point, that of white southerners who broke ranks and supported the newly recognized rights and freedoms of their black neighbors."